Youth, aspiration, and mobility: young people debating their potential futures in Nepal - Kölbel, A (2015)
This study is centrally concerned with young people's capacity to identify and realise promising educational and occupational pathways. Whilst it is now well established among social scientists that young people have agency, much less is known about what types of agency young people might demonstrate. Based on field research conducted in 2011-2012 with a group of young people studying, working, and living in Nepal's capital city, Kathmandu, the present study scrutinises Western-inspired approaches prevalent in the scholarship on youth which equate agency to resistance and individuality. It does so, by bringing the literature on youth agency into conversation with theoretical work on the concepts of aspiration and mobility. Through an in-depth analysis of young people's time-space-strategies, the thesis contributes to existing literature in three ways: First, it shows that young people may grow in power as they learn to fulfil social obligations and foster stronger relationships with other people. Second, it illustrates that young people's agency may not only take the form of observable practices, but may also reside in young people’s active efforts to think through their options for improving their own and other people's situation. Third, it highlights the importance of young people's spatial mobilities and immobilities in negotiating various social pressures and in developing a sense of themselves as competent, educated, and successful people. The findings of this thesis are, therefore, of relevance to the interdisciplinary field of youth studies as well as to emerging debates in geography about the apparent need to produce 'aspirational citizens' and about the meanings attached to spatial (im)mobility in contemporary societies.